Do Government Efforts and Commitments Affect the SDGs? - Widianingsih, Luky Patricia; Riyono, Kenley Maccauley (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the influence of three pillars of government efforts and commitment on the Sustainable Development Goals index. The three pillars are Transformation, Coordination and Multilateralism. Knowledge related to country policies should be improved to boost effectiveness to achieve better sustainable development goals. The research sample includes 74 countries around the world that have implemented Sustainable Development Goals practices so that they have a Sustainable Development Goals index achievement value and a Government Efforts and Commitment index value for the index performance period of 2023. The analysis method uses multiple regression in STATA. The results showed that only the Transformation variable had a significant effect on the achievement of the Sustainable Development Goals index, but the Coordination and Multilateralism variables had no effect. This finding confirms that comprehensive changes in sectoral policies, accompanied by concrete long-term strategic actions from all parties, are the hallmarks of the government's efforts and commitment.